Aplicação de indicadores webométricos nos programas de Pós-Graduação das engenharias recomendados pela CAPES - Silva, Ilaydiany Cristina Oliveira da (2011)
This study aims to identify, through the application of webometric indicators, which Post-Graduate Courses in Engineering recommended by the Coordination of Improvement of Higher Personnel Education (CAPES) in Brazil stand out in the web space, in relation to the communication process and dissemination of scientific information in the academic environment. For this, we analyzed the structures content of the sites, the use, through the conduct of investigations and searches, the quality of information available, as well as the structure of existent hypertexts in the sites of this universe of search. The tools and methodologies adopted for this study are: search engines (Google, Yahoo), Mapper software (Xenu Link Sleuth) and analysis software and visualization of networks (and Ucinet6 NetDraw). Webometric indicators are also used, such as size of the web sites, visibility, web impact factor, brightness and density of the network. These instruments provide a brief analysis and evaluation for this webometric study. Therefore, from the incursion of the literature used, it appears that there are many advantages of using this type of metric study in the so called Information Society. The obtained results could identify which postgraduate courses in engineering has a better availability of their information on the Web, as well to define which of these courses stands out in relation to the use of their information, which has been outstanding in respect to its impact factor and which offers a greater number of links that serve as a source of information for its users, contributing, in its turn, with the navigability of the same network. In summary, it is asserted that the webometric study presents promising results, which are able to achieve the proposed objectives, as well as identify the factors that contribute significantly to the good visualization of these sites in the network, thus helping the spread of information and scientific communication through the use of the Web.